EFFECTIVENESS OF CONCEPT ATTAINMENT MODEL BASED ON MULTIPLE REPRESENTATION TO CONCEPTUAL UNDERSTANDING AND SCIENTIFIC CONSISTENCY OF STUDENT ON WORK AND ENERGY TOPIC - MARYANA, ANA (Inovasi Pendidikan Fisika, 2017)
The physics learning systems in most schools are too oriented in mathematical problems solving, this condition make students are weak in conceptual understanding and solved problems which is present in graph, tables, or verbal representation. Thats why the aims of this research was to describe the effectiveness of concept attainment model based on multiple representation for conceptual understanding and scientific consistency of the students. The design of this research is one group pre-test post-test  design with two classes of replication. Conceptual understanding and scientific consistency was measured by multiple choiche test based on multiple representation, where there is six indicator and in each indicator were present in three problems with verbal, graph, and mathematics representation. The result of Z test shown that conceptual understanding of experiment, 1st replication, and 2nd replication classes are more than the minimum evaluation score (KKM) which is more than 65. The result of normalized gain analyze show that there is an increase in moderate category both in experiment or replication class. Based on scientific consistency analyse, there is an increase on moderate category of scientific consistency, with the score gain of experiment is 0,60 , 1st replication is 0,56 , and also 2nd replication is 0,57. In the other hand there was a good respons from the student to the learning process, shown by the percentage of the students response questsionere  which have 77% percentage in strong category. So there is a conclusion that the concept attainment model based on multiple representation was effective for conceptual understanding and scientific consistency of the students. Beside of that from this research we also found that there is a dependency of conceptual understanding and scientific consistency of the students. Keywords       :Concept Attainment, Multiple Representation, Conceptual Understanding, Scientific                 Concistency